Antibacterial Activity Test of Papaya Seed Extract (Carica papaya L.) on the Growth of Aeromonas hydrophila - Lukman Basir; Morina Riauwaty; Henni Syawal (Jurnal Perikanan dan Kelautan, 2026)
Aeromonas hydrophila is a pathogenic bacterium that can cause systemic disease and mass death. The disease caused by A. hydrophila bacteria is MAS (Motile Aeromonas Septicemia). One alternative treatment for A. hydrophila infection in fish is papaya seed extract (Carica papaya L.). This research was conducted from June 2024 to June 2025 at the Laboratory of Parasites and Fish Diseases, Aquaculture, Faculty of Fisheries and Marine, Universitas Riau. The purpose of this study was to determine the inhibition zone of papaya seed extract, as seen from the inhibition zone formed in inhibiting the growth of A. hydrophila, and also to determine the best MIC dose that can inhibit the growth of A. hydrophila. As well as to get a safe dose by conducting LD50 tests of papaya seed extract within 24 hours against common carp (Cyprinus carpio) with immersion techniques. The research method used was the experimental method, using the Kirby-Bauer disc method and a 6 mm diameter blank disk, with 3 repetitions per treatment. The results of the research indicate that papaya seed extract can inhibit the growth of A. hydrophila bacteria at concentrations of 100% - 1%, with an average inhibition zone diameter of 9, 86-6.2 mm. The MIC (Minimum Inhibition Concentration) of papaya seed extract inhibits the growth of A. hydrophila at 3.5%, with an average bacterial colony count of 280 CFU/mL. The LD50 value of papaya seed extract against common carp with the immersion technique for 24 hours is at a concentration of 3.73%.